Browse Groups

• In another attempt to derive an unorthodox factoring algorithm, I came up with the following identity. If z = x y = r**2 + d, then x * ( x + y - 2 * r) = ( r
Message 1 of 1 , Aug 1, 2008
View Source
In another attempt to derive an unorthodox factoring algorithm,

I came up with the following identity.

If z = x y = r**2 + d,

then

x * ( x + y - 2 * r) = ( r - x) **2 + d

Proof

x * (x + y - 2 * r) = x**2 + x y - 2 * x * r = x**2 + z - 2 * x * r
= x**2 - 2 * x * r + z
= x**2 - 2 * x * r + r**2 + d = ( r - x)**2 + d

Kermit
Your message has been successfully submitted and would be delivered to recipients shortly.
• Changes have not been saved
Press OK to abandon changes or Cancel to continue editing
• Your browser is not supported
Kindly note that Groups does not support 7.0 or earlier versions of Internet Explorer. We recommend upgrading to the latest Internet Explorer, Google Chrome, or Firefox. If you are using IE 9 or later, make sure you turn off Compatibility View.